Epidemiological Response to Diphtheria Cases in Sleman District, 2024 - Assaad, Andi Ratu Boelqiah; Maziyya, Arifah Alfi; Khoirunnisa; Hidayat, Wachid Nur; Dharmawidjaja, Isa; Oktaria, Vicka (BKM Public Health and Community Medicine, 2024)
Purpose: Diphtheria is an infectious disease caused by the bacterium Corynebacterium diphtheriae, which can lead to complications and death, but can be prevented through immunization. In Sleman, there have been no reported cases for many years. However, in 2024, several cases with symptoms of diphtheria. This triggered an epidemiological response to confirm outbreaks, identify close contacts, and implement control measures. Methods: A descriptive analysis was conducted using diphtheria registration data from the Sleman District Health Office from January to May 2024. Diphtheria suspected cases were defined as individuals or persons exhibiting symptoms of pharyngitis, tonsillitis, laryngitis, tracheitis, or a combination of these, accompanied by fever or without fever, and the presence of a grayish-white pseudomembrane that is difficult to remove, bleeds easily when manipulated, and has been screened by the Expert Committee from the Ministry of Health Indonesia. Laboratory-confirmed diphtheria cases were defined as suspected cases with positive results. Results: An epidemiological investigation was conducted from January 23rd to May 8th 2024, which identified 21 suspected diphtheria cases. The cases were located in the Depok, Ngaglik, Tempel, Ngemplak, Kalasan, and Seyegan sub-districts. All cases underwent oropharyngeal swabs, with 3 confirmed positive and an outbreak declared. Laboratory-confirmed cases received Anti Diphtheria Serum (ADS), treatment, and isolation. Suspected cases received prophylaxis, immunization, and quarantine. Evaluation of diphtheria immunization status revealed that 66,7% of suspected cases had been immunized. Conclusions: A diphtheria outbreak has occurred in Sleman, and control measures have been well implemented. It is recommended to conduct immunization campaigns in areas with low coverage, improve community-based education related to diphtheria through training and health promotion media, and strengthen the surveillance system through regular training for surveillance officers, optimal active case finding, and timely reporting.